PUBLIC PARTICIPATION IN BUDGET OVERSIGHT: A CASE STUDY OF PUBLIC INFORMATION DISCLOSURE IN THE NTT PROVINCIAL GOVERNMENT - Daniel Tonu (RADJA PUBLIKA, 2025)
This study evaluates the dynamics of public participation in budget oversight in East Nusa Tenggara (NTT) Province from 2021 to 2025, focusing on the effectiveness of public information disclosure as an instrument of social control. Through an in-depth analysis of the Public Information Disclosure Index (IKIP) and social audit activities conducted by civil society organizations, this study found a positive correlation between the institutional strengthening of the Information and Documentation Management Officer (PPID) and the intensity of public oversight. Although the NTT Provincial Government successfully achieved the